Atlantoaxial bands in small breed dogs: influence of external pressure by the endotracheal tube tie. (20th January 2020) - Kim, Y. J.; Lee, S.; Jung, J.; Jung, H.; In, S.; Chang, J.; Chang, D.; Fahie, M.
Abstract : Objectives: To determine the prevalence of dorsal cervical spinal compression in a population of dogs susceptible to caudal occipital dysplasia. To determine whether endotracheal tube ties iatrogenically alter the dorsal compression ratio in the atlantoaxial region. Materials and Methods: Prospective, randomised, controlled, cross‐over, blinded cohort study of dogs weighing <15 kg and presenting for neurologic signs localised to the cervical region. In mid‐sagittal T2‐weighted MR images, dorsal cervical compression and cerebellar compression were evaluated. Dorsal cervical compression ratios were calculated and compared to determine the effect of the endotracheal tube tie on the atlantoaxial region depending on whether dogs were in extended or flexed neck position. Results: Prevalence of dorsal cervical spinal compression consistent with an atlantoaxial band was 32/44 (73%) dogs without tie pressure and 37/44 (84%) dogs with tie pressure. Significantly higher compression ratios were found with tie placement over the craniocervical region. Dorsal compression ratios of dogs with cerebellar compression were significantly greater than those without it. Clinical Significance: The location of the endotracheal tube tie can influence interpretation of MR images of the craniocervical region of small breed dogs. These breeds more often had greater dorsal cervical spinal compression with tie pressure, especially when they had cerebellar compression.